Intraoperative allogeneic transfusion is associated with postoperative delirium in older patients after total knee and hip arthroplasty - OuYang, Chun-lei; Hao, Xin-yu; Yu, Yao; Lou, Jing-sheng; Cao, Jiang-bei; Yu, Ying-qun; Mi, Wei-dong (Frontiers in Surgery, 2023)
Objective To determine whether intraoperative transfusion of allogeneic or autologous blood is associated with an increased incidence of postoperative delirium (POD) after total knee arthroplasty (TKA) and total hip arthroplasty (THA). Methods The medical records of 1,143 older (≥65 years old) patients who received an intraoperative blood transfusion while undergoing total knee or hip arthroplasty at the First Medical Center of Chinese PLA General Hospital from 2014 to 2019 were reviewed; of these patients, 742 (64.92%) received allogeneic blood, while 401 (35.08%) received autologous blood. Patients who received autologous transfusion were paired with those received allogeneic transfusion using 1:1 propensity score matching method. The primary outcome was POD. The secondary outcomes were postoperative complications, including heart failure, deep vein thrombosis, myocardial infarction, stroke, and lung infection. Multivariable nominal logistic regression was used to identify any independent associations between intraoperative blood transfusions and POD, and secondary postoperative complications, respectively. Results Postoperative delirium occurred in 6.6% (49/742) of patients who had received an allogeneic blood transfusion and in 2.0% (8/401) of patients who had received an autologous blood transfusion. It is noteworthy that the multivariable logistic regression demonstrated a significant association between intraoperative allogeneic blood transfusion and POD (odds ratio [OR]: 4.11; 95% confidence interval [CI]: 1.95–9.77; p < 0.001). After PSM, Allogeneic transfusion was also the strongest predictor for POD (OR: 4.43; 95% CI: 2.09–10.58; p < 0.001). Conclusions In the patients who had received THA or TKA, intraoperative allogeneic blood transfusions were associated with an increased risk of POD.